Knowledge, Attitudes, and Motivation Associated with Hypertension Self-Care Adherence Among Older Adults: A Cross-Sectional Study - Suaib Suaib; Dian Meiliani Yulis (Edukasi Ilmiah Indonesia, 2025)
Introduction: Hypertension remains one of the leading chronic conditions affecting older adults and requires sustained self-care adherence to prevent cardiovascular and renal complications. Multiple behavioral factors influence adherence, yet evidence regarding the contribution of knowledge, attitudes, and motivation among Indonesian older adults remains limited. This study aimed to examine the associations between knowledge, attitudes, motivation, and self-care adherence among older adults with hypertension in Palu, Indonesia. Methods: A community-based cross-sectional study was conducted between May and June 2026 involving 72 older adults with hypertension selected through accidental sampling from a population of 250 eligible patients. Data were collected using structured questionnaires assessing knowledge, attitudes, motivation, and self-care adherence. Descriptive statistics summarized participant characteristics, while Chi-square tests and odds ratios (ORs) with 95% confidence intervals (CIs) were used to evaluate associations. Statistical significance was established at p<0.05. Results: Most participants demonstrated good knowledge (59.7%), positive attitudes (62.5%), high motivation (66.7%), and adherence to hypertension self-care (63.9%). Good knowledge was significantly associated with greater adherence (OR=9.77; 95% CI: 3.05–31.35; p<0.001). Participants with positive attitudes were more likely to adhere to recommended self-care practices (OR=12.89; 95% CI: 3.85–43.17; p<0.001). High motivation showed the strongest association with adherence (OR=35.00; 95% CI: 8.36–146.59; p<0.001). Conclusion: Knowledge, positive attitudes, and motivation were significantly associated with self-care adherence among older adults with hypertension. Strengthening patient education, motivational counseling, family engagement, and continuous follow-up may improve long-term adherence and contribute to better hypertension management in primary healthcare settings